2008
DOI: 10.2147/cia.s820
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in the aging male: Treatment options

Abstract: In elderly women, loss in bone mass and micro-architectural changes are generally attributed to the onset of menopause. Men do not experience menopause, they do, however, experience age-related acceleration in bone loss and micro-architecture deterioration. The incidence of osteoporotic fractures in elderly men, just as in aged women, increases exponentially with age; the rise in men, however, is some 5–10 years later than in women. Up to 50% of male osteoporotics have no identifiable etiology; however elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 83 publications
2
30
0
Order By: Relevance
“…Approximately half the male patients with osteoporosis presenting with symptomatic VFs have identifiable secondary causes [4]; GC therapy is a common cause of osteoporosis in older men [5]. The prevention of fractures in men seems to be much more important than in women because male mortality rates within 1 or 2 years after a fracture are higher than in females [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half the male patients with osteoporosis presenting with symptomatic VFs have identifiable secondary causes [4]; GC therapy is a common cause of osteoporosis in older men [5]. The prevention of fractures in men seems to be much more important than in women because male mortality rates within 1 or 2 years after a fracture are higher than in females [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Alendronate (Fosamax) is approved in USA for use in men and has been shown to increase BMD with a trend toward reduction of non-vertebral and vertebral fracture risk [96]. Risedronate (Actonel] is often used in men with chronic steroid use and it has been shown to increase BMD in men as well [97,98].…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…There have been significant advances in the prevention of fracture in women, but the same cannot, as yet, be said for men. Over the past decade, osteoporosis in men has come to be increasingly recognised as a clinical and public health concern, and a much neglected area of study [5][6][7][8] The aetiology of bone fragility in men compared to women has received less attention in the literature [6,[9][10][11][12]. The diagnostic threshold for osteoporosis in men-and its treatment-is based on studies in women [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of evidence from large-scale, randomised, controlled clinical trials, fracture-prevention treatment recommendations for men remain open to consideration [11]. Several small studies have shown improvements in surrogate endpoints using pharmacological therapies such as bisphosphonates, human parathyroid hormone and calcium and vitamin D supplementation [6,11,[14][15][16][17]. For example, bisphosphonates increase BMD in men at the spine and proximal femur [16], and among older men with hip fracture, intravenous bisphosphonates therapy reduces overall risk of fracture [18].…”
Section: Introductionmentioning
confidence: 99%